Comparison of diagnostic performances of different serological tests for SARS‐CoV‐2 antibody detection in cats and dogs. Issue 6 (13th October 2022) - Ratti, Gabriele; Lelli, Davide; Moreno, Ana; Stranieri, Angelica; Trogu, Tiziana; Giordano, Alessia; Grassi, Andrea; Luzzago, Camilla; Decaro, Nicola; Paltrinieri, Saverio; Lauzi, Stefania
Abstract: Serosurveillance among animals, including pets, plays an important role in the current coronavirus disease 2019 (COVID‐19) pandemic, because severe acute respiratory coronavirus 2 (SARS‐CoV‐2) infections in animal populations could result in the establishment of new virus reservoirs. Serological assays that offer the required sensitivity and specificity are essential. In this study, we evaluated the diagnostic performance of three different commercially available immunoassays for the detection of SARS‐CoV‐2 antibodies in pets, namely two ELISA tests for the detection of antibodies against SARS‐CoV‐2 nucleocapsid [ID Screen SARS CoV‐2 double antigen multispecies (Double antigen) and ID Screen® SARS‐CoV‐2‐N IgG indirect ELISA (Indirect)] and one test for the detection of neutralizing antibodies against SARS‐CoV‐2 receptor‐binding‐domain [surrogate virus neutralization test (sVNT)]. The obtained results were compared with those of conventional virus neutralization test (VNT), which was regarded as reference method. A total of 191 serum samples were analysed. Thirteen (6.8%) samples showed VNT‐positive results. The overall sensitivity was higher for sVNT (100%) compared to nucleocapsid‐based ELISA assays (23% for Double antigen and 60% for Indirect). The specificity was 100% for Indirect ELISA and sVNT, when a higher cut‐off (>30%) was used compared to the one previously defined by the manufacturer (>20%), whereas the other test showed lower value (99%). The sVNT test showed the highest accuracy and agreement with VNT, with a perfect agreement when the higher cut‐off was applied. The agreement between each nucleocapsid‐based ELISA test and VNT was 96% for Indirect and 94% for Double antigen. Our findings showed that some commercially available serological tests may lead to a high rate of false‐negative results, highlighting the importance of assays validation for the detection of SARS‐CoV‐2 antibodies in domestic animals.